Digitisation and Language Technologies in the Learning Process of Information Sciences – Approaching the EU Standards - Stančić, Hrvoje; Seljan, Sanja; Lasić-Lazić, Jadranka (2007)
The authors discuss the need for digital content that represents basis for multilingual and multicultural environment enabling multilingual information retrieval and computer-assisted translation. The authors examine the learning process of information sciences at Croatian university level education in correlation with the European context. The problem of multilingualism in the information society has been investigated in the context of the Bologna process and the requirement of the student mobility as well as in the context of different EU standards, action plans and framework programmes. Further, the authors describe e-learning environment implemented at the university level, give the results of the research made among the users of the system, and discuss the potential problems considering the digitisation in the process of preparation of the materials in order to enable the application of language technologies for automatic translation suitable in the student mobility environment.
CD - L’ enseignement supérieur et la recherche face aux enjeux de la société du savoir
Projekt MZOS
Projekt MZOS
ENG